ニホン ナンキョク チイキ カンソクタイ ニ オケル イガク ケンキュウ ノ ケイイイ ト ショウライ テンボウ - 森本, 武利; モリモト, タケトシ; 佐藤, 克文; サトウ, カツフミ; 大野, 秀樹; オオノ, ヒデキ; 福地, 光男; フクチ, ミツオ; Morimoto, Taketoshi; Sato, Katsufumi; Ohno, Hideki; Fukuchi, Mitsuo (2002)
P(論文) 「南極における医学研究の将来展望に関する研究小集会」を, 平成13年8月23日, 国立極地研究所講義室において開催した。参加者は13名であった。これまでの南極地域観測隊における医学研究成果, および平成13年に出発する第43次南極地域観測隊における医学研究計画が報告された。本研究小集会を機に, これまでの医学研究の経緯と研究業績をまとめ, 将来への発展を展望した。また, 研究計画立案過程の際のいくつかの改善すべき点についてまとめた。 A workshop on Medical Research by the Japanese Antarctic Research Expedition (JARE) was held on August 23,2001,at the National Institute of Polar Research with 13 participants. Recent progress in medical research was introduced and the plan of the 43rd JARE was discussed. Previous achievements in the medical research were summarized and future prospects were discussed. To make further progress in medical research by JARE. some improvements in planning should be developed in the near future. departmental bulletin paper